2015
DOI: 10.1177/0192512115571590
|View full text |Cite
|
Sign up to set email alerts
|

The roles of Eurosceptic Members of the European Parliament and their implications for the EU

Abstract: The 2014 European elections demonstrated the scale and success of the EU's opponents. Radical and populist parties topped the polls in some countries while others gained parliamentary representation for the first time. At the same time, Euroscepticism has entered the mainstream, with an increase of anti-EU rhetoric among government parties and the European Conservative and Reformist group becoming the third largest party in the European Parliament. In this context, this article aims at analysing the strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…This article has presented an analysis of Eurosceptic MEPs' behaviour in trilogues and how mainstream political groups react to higher levels of polarisation. To this end we used Taggart and Szcerbiak's (2004;Szczerbiak and Taggart 2008) differentiation between soft and hard Euroscepticism and combined it with Brack's (2013Brack's ( , 2015 four ideal-types of Eurosceptic MEPs as a starting point for an inductive examination of Eurosceptic MEPs in trilogues. The analysis revealed that pragmatist or participant Eurosceptic MEPs are present and actively involved in trilogues; Eurosceptic MEPs acting as public orators or absentees do not participate in trilogues or even try to disrupt them.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article has presented an analysis of Eurosceptic MEPs' behaviour in trilogues and how mainstream political groups react to higher levels of polarisation. To this end we used Taggart and Szcerbiak's (2004;Szczerbiak and Taggart 2008) differentiation between soft and hard Euroscepticism and combined it with Brack's (2013Brack's ( , 2015 four ideal-types of Eurosceptic MEPs as a starting point for an inductive examination of Eurosceptic MEPs in trilogues. The analysis revealed that pragmatist or participant Eurosceptic MEPs are present and actively involved in trilogues; Eurosceptic MEPs acting as public orators or absentees do not participate in trilogues or even try to disrupt them.…”
Section: Resultsmentioning
confidence: 99%
“…Other soft Eurosceptics insist on the importance of national interests trying to defend or stand up for it during debates or parliamentary work (Szczerbiak and Taggart 2008;Taggart and Szczerbiak 2004). 2 While a categorisation of different nuances of Euroscepticism is important for an analysis of Eurosceptic parties and/or MEPs, it fails to explain Eurosceptics' attitudes inside the EP, especially when it comes to voting behaviour, coalition formation or their behaviour in plenary compared to committees (Almeida 2010;Brack 2015;Vasilopoulou 2013; Whitaker and Lynch 2014). Brack has filled this gap by developing a typology of Eurosceptic MEPs based on their different approaches to parliamentary work (Brack 2013(Brack , 2015Costa and Brack 2009).…”
Section: Eurosceptics In the Ep: Voting Behaviour Coalitions And Strmentioning
confidence: 99%
“…There was, certainly, a spectrum of Euroscepticism among these parties, ranging from hard Eurosceptics who wished to abolish the EU to soft Eurosceptics who advocated for an alternative political model (Taggart 1998;Szczerbiak and Taggart 2008). This also translated into different types of behaviour once they joined the EP: from those who were never there, to those who used the EP as a tribune to propagate their Eurosceptic ideas, and a large majority who took a more pragmatic view and participated in parliamentary life like any other mainstream MEP (Brack 2015(Brack , 2012. However, the rising number of MEPs sitting on the extremes of the ideological spectrum narrowed the field for building compromises among mainstream parties.…”
Section: Ep Empowerment Under the Shadow Of Populismmentioning
confidence: 99%
“…Overall, we expected, however, that placement on the EU integration dimension would mater more than GAL–TAN position to explain MEPs’ voting behaviour in security issues. This would happen because how a national party relates to EU integration generally and to measures proposed by the EU actors shapes their reactions prior to judging the content of the measures (Brack, , p. 341). Thus, even if a more authoritarian‐leaning party values security measures, if it is Eurosceptic it would be reluctant to endorse them because they bring along ‘more Europe’.…”
Section: Theoretical Frameworkmentioning
confidence: 99%